2019
DOI: 10.5812/thrita.88367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aβ Deposits in the Hippocampus of a Rat Model of Alzheimer’s Disease After Intravenous Injection of Human Adipose Derived Stem Cells by Immuno- and Thioflavin S-Costaining

Abstract: Background: Alzheimer's disease (AD) is a progressive neuropsychiatric disorder that gradually impairs memory and behavioral functions. Amyloid beta (Aβ) is considered as the most toxic substance in the brain of AD patients. Objectives: The present study was designed to evaluate Aβ deposits by Immuno-and Thioflavin S-costaining in the hippocampus of a rat model of AD after intravenous injection of human adipose-derived stem cells (hADSCs). Methods: Thirty-two male rats were included in the four groups of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The systematic and manual search in databases resulted in 1134 articles, of which 789 were non‐duplicated. Next, the title and abstract screen were performed to eliminate 770 articles, and from the remaining 19 articles, 10 were included in our systematic review 16 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 (Figure 1 ). From the included studies, five were performed on rats and five were performed on mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic and manual search in databases resulted in 1134 articles, of which 789 were non‐duplicated. Next, the title and abstract screen were performed to eliminate 770 articles, and from the remaining 19 articles, 10 were included in our systematic review 16 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 (Figure 1 ). From the included studies, five were performed on rats and five were performed on mice.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, seven articles evaluated the therapeutic effects of ADSCs in different animal models of AD. 16 , 22 , 26 , 30 , 31 , 32 , 33 Although an explicit meta‐analysis was not applicable to the included results, an overview of these investigations could help to understand the potential effects and mechanisms of ADSCs administration in experimental models of AD. These studies evaluated the behavioral tests as well as histopathological assessments in AD animal models after application of ADSCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research revealed the same findings. [ 16 ] Investigations suggest that there are many reasons for AD; therefore, aiming the neurodegeneration process is important, as it may have useful effects in developing new strategies for the treatment of AD. Neuronal loss is a crucial characteristic of AD and is constantly found in various regions of the brain.…”
Section: Discussionmentioning
confidence: 99%